2015
DOI: 10.1111/syen.12139
|View full text |Cite
|
Sign up to set email alerts
|

Molecules, morphology and Mimeoma scarabs: evolutionary and taxonomic implications for a palm‐associated scarab group

Abstract: Abstract. Cyclocephaline scarabs, the second largest tribe of rhinoceros beetles, are important pollinators of early-diverging angiosperm families in the tropics. The evolutionary history of cyclocephaline genera is poorly resolved and several genera are thought to be nonmonophyletic. We assess the monophyly of Mimeoma Casey, a group of Neotropical palm-feeding scarabs, and its relationship to Cyclocephala with a phylogenetic analysis of 2899 bp of DNA sequence data and 18 morphological characters. All five sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…These species were placed into the “ helleri species-group” based on the bidentate form of the protibial margin in males. This male protibial character is shared with species formerly included in Mimeoma and some Cyclocephala species (like C. amazona ) (see Moore et al 2015). The dorsal coloration of the “ helleri species-group”, especially the elongated, triangular maculae found along the elytral suture, is like that found in some former Mimeoma species (especially Cyclocephala acuta Arrow and C. englemani (Ratcliffe)).…”
Section: Generic Overviewsmentioning
confidence: 76%
See 2 more Smart Citations
“…These species were placed into the “ helleri species-group” based on the bidentate form of the protibial margin in males. This male protibial character is shared with species formerly included in Mimeoma and some Cyclocephala species (like C. amazona ) (see Moore et al 2015). The dorsal coloration of the “ helleri species-group”, especially the elongated, triangular maculae found along the elytral suture, is like that found in some former Mimeoma species (especially Cyclocephala acuta Arrow and C. englemani (Ratcliffe)).…”
Section: Generic Overviewsmentioning
confidence: 76%
“…Breeschoten et al (2013) presented a morphological phylogeny of cyclocephaline genera, but few details of the analysis were provided and the support for recovered relationships were not reported. Moore et al (2015) suggested that Mimeoma species were nested among a clade of Cyclocephala that included the type species of the genus, C. amazona . These data also provided evidence of two major clades of Cyclocephala based on morphological and molecular evidence (Moore et al 2015).…”
Section: Evolution and Fossil Recordmentioning
confidence: 99%
See 1 more Smart Citation
“… Arrow 1902 , 1937b , Blackwelder 1944 , Pike et al 1976 , Endrődi 1966 , 1985a , Bullock 1981 , Beach 1984 , Morón et al 1985 , Thomas 1993 , Ratcliffe and Morón 1997 , Ratcliffe 2002a , 2003 , Restrepo et al 2003, Ratcliffe and Cave 2006 , Neita-Moreno 2011 , Krajcik 2005 , 2012 , Moore 2012 , Ratcliffe et al 2013 , Moore et al 2015 , Gasca-Álvarez and Deloya 2016 .…”
Section: Annotated Catalog and Bibliography Of The Cyclocephaline Scamentioning
confidence: 99%
“… Burmeister 1847 , Harold 1869b , Höhne 1923b , Arrow 1937b , Blackwelder 1944 , Pike et al 1976 , Endrődi 1966 , 1985a , Silberbauer-Gottsberger et al 2001 , Ratcliffe 2002a , 2003 . Neita-Moreno et al 2006 , Ratcliffe and Cave 2006 , Neita-Moreno 2011 , Otavo et al 2013 , Ratcliffe et al 2013 , López-García et al 2015 , Moore et al 2015 , Deloya et al 2014a , 2016 , Gasca-Álvarez and Deloya 2016 , Hielkema 2017 .…”
Section: Annotated Catalog and Bibliography Of The Cyclocephaline Scamentioning
confidence: 99%